2017
DOI: 10.18632/oncotarget.18109
|View full text |Cite
|
Sign up to set email alerts
|

Aging-dependent DNA hypermethylation and gene expression of GSTM1 involved in T cell differentiation

Abstract: This study investigated whether aging was associated with epigenetic changes of DNA hypermethylation on immune gene expression and lymphocyte differentiation. We screened CG sites of methylation in blood leukocytes from different age populations, picked up genes with age-related increase of CG methylation content more than 15%, and validated immune related genes with CG hypermethylation involved in lymphocyte differentiation in the aged population. We found that 12 genes (EXHX1、 IL-10、 TSP50、 GSTM1、SLC5A5、SPI1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…While epigenetic changes in aging result in largely unpredictable changes in gene expression, some of these likely represent unidirectional adaptive changes that contribute to the basic biological underpinning of aging [83, 84]. Recent studies focusing on transcriptomic approaches have confirmed that age-associated methylation changes vary depending on the specific leukocyte populations and T cell subsets [85, 86]. Amongst the various immune cell populations, the T cell compartment may be most affected by the aging process [86, 87].…”
Section: Age-related Changes In the Immune Systemmentioning
confidence: 99%
“…While epigenetic changes in aging result in largely unpredictable changes in gene expression, some of these likely represent unidirectional adaptive changes that contribute to the basic biological underpinning of aging [83, 84]. Recent studies focusing on transcriptomic approaches have confirmed that age-associated methylation changes vary depending on the specific leukocyte populations and T cell subsets [85, 86]. Amongst the various immune cell populations, the T cell compartment may be most affected by the aging process [86, 87].…”
Section: Age-related Changes In the Immune Systemmentioning
confidence: 99%
“…[ 11 16 17 18 20 ] The same studies showed an increase in the percentage of methylation of this gene with age. [ 11 16 17 18 20 ] The percentage of hypermethylation was calculated manually. This was done in contrast to different studies that used software to do the same.…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, NPTX2 methylation status was shown to be linked with age in blood as well. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in patients with anaplastic astrocytoma as well as oligodendroglioma, the GSTM1-null genotype, in combination with a specific homozygous GSTM1 allelic variant, infers superior survival and increased chemotherapy-related toxicity (30). More recent studies have associated GSTM1 mRNA levels with type 1 Th cell differentiation in aging (31), suggesting that GSTM1 deficiency may effect CD4 T cell function. The exact mechanism of GSTM1 and if GSTM1 deletion is a predictor of vaccination response in children with recurrent LGG remain to be elucidated in a larger cohort.…”
Section: Discussionmentioning
confidence: 99%